The role of off‐focus radiation in scatter correction for dedicated cone beam breast CT - Shi, Linxi (John Wiley and Sons Inc., 2017)

(untitled) (Med Phys)
PURPOSE: Dedicated cone beam breast CT (CBBCT) suffers from x‐ray scatter contamination. We aim to identify the source of the significant difference between the scatter distributions estimated by two recent methods proposed by our group and to investigate its effect on CBBCT image quality. METHOD: We recently proposed two novel methods of scatter correction for CBBCT, using a library based (LB) technique and a forward projection (FP) model. Despite similar enhancement on CBBCT image qualities, these two methods obtain very different scatter distributions. We hypothesize that the off‐focus radiation (OFR) is the contributor and results in nontrivial signals in x‐ray projections, which is ignored in the scatter estimation via the LB method. Experiments using a thin wire test tool are designed to study the effect of OFR on CBBCT spatial resolution by measuring the point spread function (PSF) and the modulation transfer function (MTF). A narrow collimator setting is used to suppress the OFR‐induced signals. In addition, “PSFs” and “MTFs” are measured on clinical CBBCT images obtained by the LB and FP methods using small calcifications as point sources. The improvement of spatial resolution achieved by suppressing OFR in the wire experiment as well as in the clinical study is quantified by the improvement ratios of PSFs and spatial frequencies at different MTF values. Our hypothesis that OFR causes the imaging difference between the FP and LB methods is verified if these ratios obtained from experimental and clinical data are consistent. RESULTS: In the wire experiment, the results show that suppression of OFR increases the maximum signal of the PSF by about 14% and reduces the full‐width‐at‐half‐maximum (FWHM) by about 12.0%. Similar improvement on spatial resolution is achieved by the FP method compared with the LB method in the patient study. The improvement ratios of spatial frequencies at different MTF values without OFR match very well in both studies at a level of around 16%, with an average root‐mean‐square difference of 0.47%. CONCLUSION: The results of the wire experiment and the clinical study indicate that the main difference between the LB and FP methods is whether the OFR‐induced signals are included after scatter correction. Our study further shows that OFR significantly affects the image spatial resolution of CBBCT, indicating that the visualization of micro‐calcifications is susceptible to OFR contamination. Our finding is therefore important in further improvement of diagnostic performance of CBBCT.